Hereditary breast cancer Das hereditäre Mammakarzinom - Crohns, C.; Mundhenke, Christoph (Gynäkologe, 2009)
About 10% of all breast cancer cases are of genetic origin. A positive family history for breast and/or ovarian cancer can strongly hint at a hereditary background. Mutation in BRCA1 or BRCA2 raises the relative lifetime risk of breast cancer to 80%. Furthermore, there is a significant risk of other mutation-associated cancers; the ovarian cancer lifetime risk is up to 45%. Knowledge of a hereditary cause for breast cancer in a patient's own or family history influences early cancer detection, prevention strategies, therapy, and aftercare. New therapy options such as the PARP-1 inhibitor, the first specific and molecular target, and the use of platinum-based drug regimens to individualize treatment of BRCA-associated cancer are now being tested in clinical trials. The data for all families that have undergone genetic counseling are being collected by the German Consortium for Hereditary Breast and Ovarian Cancer to enable participation in clinical research and in the worldwide search for new high-risk genes.
CRIS-Team Scopus Importer:2022-11-17
Keywords: BRCA1-gene; BRCA2-gene; Early cancer detection; Genetic testing; Hereditary breast cancer